Acoso laboral en el ejercicio periodístico. Caso. Caravana 2022 - Cartagena Silva, Erika Nayely (2022)
This case study has been developed on the concept of labor harassment of women in journalism. Case Caravana 2022. Since it is a type of violence that restricts the exercise of their rights and seriously impairs the quality of life of a person. Despite the existence of laws and organizations that sanction labor and sexual harassment, little attention is paid to this issue in Ecuador. The methodology used in this work is qualitative and since the topic of study has sufficient theoretical basis, it was decided to use a non-experimental design that would be applied transversally, the technique used is the interview with the participation of two journalists and two legal professionals. By means of the conclusion where the main points were covered and for this the interview technique was used where an analysis was obtained with effective results and thanks to this study technique it was possible to gather important and necessary information from both the professionals in the legal area and the journalists, where it can be concluded that women journalists by the simple fact of being women are more vulnerable to harassment at work. It can also be concluded that people who suffer some kind of harassment in the journalistic exercise, where they can go and be taken into account is in the foundations such as Periodistas Sin Cadenas, Fundamedios and Red de Periodistas Libres so that in one way or another their cases do not remain invisible.